Литі монети Ольвії з Деметрою - Орлик, О. (Ośrodek Badań Europy Środkowo-Wschodniej, 2022)
У дослідженні розглянуті тетроболи, і знайдено значну кількість різних варіацій, що вказує на значний масштаб емісій даного типу монет із Деметрою. Вже у пізніші періоди карбованими були мідні, а також срібні та золоті монети із зображенням Деметри. Загалом у 1 пол. IV ст. до н. е. образ Деметри здобув значне поширення у монетній справі Ольвії. The study examined tetrobols and found a significant number of different variations, indicating a significant scale of issues of this type of coins with Demeter. Already in later periods, copper, as well as silver and gold coins with the image of Demeter were minted. In general, in 1 gender. IV century to n. e., the image of Demeter became widespread in the coinage of Olbia.
Cast coins of Olbia with Demeter
Keywords: Монети; Тетроболи; Ольвія; Coins; Tetrobols; Olbia